EVOLUTION OF THE WORLD EXPERIENCE OF THE INSTITUTE OF STATE AND CITIZEN COMMUNICATION - Tashpulatovich, Kalkanov Nuriddin; Egamberdievich, Hujamberdiev Tursunpulat; Berdiboevich, Shakarov Uktam; Ismailovna, Kurbanalieva Hulkar; Karimovich, Otabaev Abdukadir (International Journal of Psychosocial Rehabilitation, 2020)
based on the experience of developed countries of the world in our country, political institutions, which are characteristic and suitable for our world national statehood, are the main objectives of the reforms carried out to ensure their full-fledged activities. In this regard, it is important to study the past historical experience of highly developed countries. This situation gives great impetus to the practical implementation of legal and regulatory documents aimed at developing the activities of state and civil society institutions in Uzbekistan and further improvement of communication with the people. We tried to briefly cover these aspects in the article.